2021
DOI: 10.1093/cvr/cvab287
|View full text |Cite
|
Sign up to set email alerts
|

Diseases of the Aorta and Kidney Disease: conclusions from a Kidney Disease: Improving Global Outcomes (KDIGO) Controversies Conference

Abstract: Chronic kidney disease (CKD) is an independent risk factor for the development of abdominal aortic aneurysm (AAA), as well as for cardiovascular and renal events and all-cause mortality following surgery for AAA or thoracic aortic dissection. In addition, the incidence of acute kidney injury (AKI) after any aortic surgery is particularly high, and this AKI per se is independently associated with future cardiovascular events and mortality. On the other hand, both development of AKI after surgery and the long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 101 publications
0
13
0
Order By: Relevance
“…The occurrence of AKI in AAD has important implications, and the adverse effect of AKI in the perioperative period has been well described for patients with AAD previously ( 20 22 ). The incidence, trends, risk factors, management, and prognosis of AAD-related AKI have been revealed in a series of studies ( 6 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The occurrence of AKI in AAD has important implications, and the adverse effect of AKI in the perioperative period has been well described for patients with AAD previously ( 20 22 ). The incidence, trends, risk factors, management, and prognosis of AAD-related AKI have been revealed in a series of studies ( 6 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of AKI in AAD has important implications, and the adverse effect of AKI in the perioperative period has been well described for patients with AAD previously ( 20 22 ). The incidence, trends, risk factors, management, and prognosis of AAD-related AKI have been revealed in a series of studies ( 6 , 20 ). Regardless of treatment strategy and definition of AKI, studies have shown that AAD-related AKI is associated with hypertension, diabetes, advanced age, gender, and arterial malperfusion, which is consistent with our findings ( 23 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative ARF creates a risk factor for immediate and late renal replacement therapy (RRT) which will affect the overall survival of patients who are treated for ATAAD repair. 11, [15][16][17][18][19] Brown et al presented the effect of ARF on the long-term survival of patients who were operated on for ATAAD under hypothermic circulatory arrest (HCA). 1 The observational study were at risk for the development of postoperative ARF.…”
mentioning
confidence: 99%
“…Recently, many studies have included postoperative ARF as the end-point for primary outcomes of patients with ATTAD. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] From May 2020 to October 2021 over 10 studies have been published with this end-point. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] The incidence of postoperative ARF was 10.5%-68.1%.…”
mentioning
confidence: 99%